2021
DOI: 10.1101/2021.05.17.444434
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Megalencephalic leukoencephalopathy with subcortical cysts is a developmental disorder of the gliovascular unit

Abstract: Absence of the astrocyte-specific membrane protein MLC1 is responsible for megalencephalic leukoencephalopathy with subcortical cysts (MLC); this rare type of leukodystrophy is characterized by early-onset macrocephaly and progressive white matter vacuolation that lead to ataxia, spasticity, and cognitive decline. During postnatal development (from P5 to P15 in the mouse), MLC1 forms a membrane complex with GlialCAM (another astrocytic transmembrane protein) at the junctions between perivascular astrocytic pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Mlc1 À/À mice display neurologic pathologies that have some similarities to early stage MLC in humans (Dubey et al, 2015), although Mlc1 À/À mice do not fully recapitulate the complex brain pathologies that typify the human disease (Hoegg-Beiler et al, 2014). A recent study has reported normal BBB integrity in Mlc1 À/À mice (Gilbert et al, 2021). In the PA-ablated mouse model we describe here, we detect more severe neurologic deficits than those described in Mlc1 À/À mice.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Mlc1 À/À mice display neurologic pathologies that have some similarities to early stage MLC in humans (Dubey et al, 2015), although Mlc1 À/À mice do not fully recapitulate the complex brain pathologies that typify the human disease (Hoegg-Beiler et al, 2014). A recent study has reported normal BBB integrity in Mlc1 À/À mice (Gilbert et al, 2021). In the PA-ablated mouse model we describe here, we detect more severe neurologic deficits than those described in Mlc1 À/À mice.…”
Section: Discussionmentioning
confidence: 44%
“…Also note the close juxtaposition of YFP 1 PAs and Iba1 1 microglia. pathologies found in Mlc1 À/À mice (Gilbert et al, 2021) and in humans with MLC1 mutations (Dubey et al, 2018). Nonetheless, it will be important to determine whether there are other brain pathologies resulting from Mlc1 1 astrocyte ablation that are independent of BBB disruption.…”
Section: Discussionmentioning
confidence: 99%
“…HepaCAM in the liver suppresses the growth of hepatocytes and is down-regulated in hepatocellular carcinoma, suggesting tumor suppressor-like functions (2). In the brain, hepaCAM is normally expressed in astrocytes where it regulates ion homeostasis (3), BBB physiology (4), and synaptic excitation (5). Putative functions for hepaCAM in the brain were discovered during genomic sequencing of patients with the neurodevelopmental brain disorder megalencephalic leukoencephalopathy with subcortical cysts (MLC) (6).…”
Section: Introductionmentioning
confidence: 99%